Medicinal Fungi with Antiviral Effect - Zhang, Yu; Zhang, Guoying; Ling, Jianya (Molecules (Basel, Switzerland), 2022)
Pandemics from various viruses make natural organisms face challenges over and over again. Therefore, new antiviral drugs urgently need to be found to solve this problem. However, drug research and development is a very difficult task, and finding new antiviral compounds is desirable. A range of medicinal fungi such as Ganoderma lucidum and Cordyceps sinensis are widely used all over the world, and they can enhance human immunity and direct anti-virus activities and other aspects to play an antiviral role. Medicinal fungi are used as foods or as food supplements. In this review, the species of medicinal fungi with antiviral activity in recent decades and the mechanism of antiviral components were reviewed from the perspectives of human, animal, and plant viruses to provide a comprehensive theory based on better clinical utilization of medicinal fungi as antiviral agents.